2023
DOI: 10.1039/d2me00165a
|View full text |Cite
|
Sign up to set email alerts
|

Design of LCST-type phase separation of poly(4-hydroxystyrene)

Abstract: Commercially available poly(4-hydroxylstyrene) was introduced as a new LCST (lower critical solution temperature)-type thermo-responsive polymer at ambient temperature. The LCST-type phase separation was designed by control of the solvation and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…100 °C), PHEMA was soluble in DMSO, DMF, methanol, ethanol, and acetic acid, while being practically insoluble in acetonitrile, 2-butanone, 1-octanol, THF, ethyl acetate, toluene, DCE and cyclohexane. In comparison to PHS in our previous study, 70 PHEMA exhibits poor solubility in solvents with moderate polarity such as THF and acetonitrile. The relatively weak hydrogen bond acceptors could not solubilize the polymer chain due to the association of hydroxy groups between the polymer chains.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…100 °C), PHEMA was soluble in DMSO, DMF, methanol, ethanol, and acetic acid, while being practically insoluble in acetonitrile, 2-butanone, 1-octanol, THF, ethyl acetate, toluene, DCE and cyclohexane. In comparison to PHS in our previous study, 70 PHEMA exhibits poor solubility in solvents with moderate polarity such as THF and acetonitrile. The relatively weak hydrogen bond acceptors could not solubilize the polymer chain due to the association of hydroxy groups between the polymer chains.…”
Section: Resultsmentioning
confidence: 65%
“…Additionally, we recently reported that poly(4-hydroxy styrene) ( PHS ), a commodity plastic, undergoes LCST-type phase separations in binary solvent mixtures of common hydrogen-bonding solvents and a non-polar solvent. 70 The phase separations are induced readily by heating, due to the dissociation of the polymer complexes as pseudo-desolvation. In particular, the thermal cleavage of the hydrogen bonds between a hydrogen-bonding functional group in the polymer chain and a hydrogen-bonding solvent plays a pivotal role in designing the desolvation of the polymer chain in the entropy-driven LCST-type phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Poly(4-hydroxystyrene) has already attracted attention for a variety of applications including photoresist materials, physical gel composites, and pH-responsive materials. [30][31][32] The direct polymerization of 4-hydroxystyrene by anionic polymerization is not viable due to the acidic nature of the hydroxyl group. Anionic polymerization provides the ability to produce narrow molecular weight distribution polymers with stoichiometric control over the molecular weight.…”
Section: Introductionmentioning
confidence: 99%